2020
DOI: 10.3390/insects11050294
|View full text |Cite
|
Sign up to set email alerts
|

DNA Metabarcoding as a Tool for Disentangling Food Webs in Agroecosystems

Abstract: Better knowledge of food webs and related ecological processes is fundamental to understanding the functional role of biodiversity in ecosystems. This is particularly true for pest regulation by natural enemies in agroecosystems. However, it is generally difficult to decipher the impact of predators, as they often leave no direct evidence of their activity. Metabarcoding via high-throughput sequencing (HTS) offers new opportunities for unraveling trophic linkages between generalist predators and their prey, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…stoichiometry). We used carbon and nitrogen as nutrients because they are essential elements in terrestrial ecosystems (Attiwill & Adams, 1993), biotic processes are intimately involved in their cycling through ecosystems (Coleman et al, 1983) and they are commonly studied in nutrient cycling studies (Koltz et al, 2018;Shi et al, 2016). Most studies we screened reported decomposition dynamics of plant litter as mass loss or remaining; thus, we only used studies where proportion mass loss of initial litter weight could be calculated.…”
Section: Literature Survey and Data Extractionmentioning
confidence: 99%
“…stoichiometry). We used carbon and nitrogen as nutrients because they are essential elements in terrestrial ecosystems (Attiwill & Adams, 1993), biotic processes are intimately involved in their cycling through ecosystems (Coleman et al, 1983) and they are commonly studied in nutrient cycling studies (Koltz et al, 2018;Shi et al, 2016). Most studies we screened reported decomposition dynamics of plant litter as mass loss or remaining; thus, we only used studies where proportion mass loss of initial litter weight could be calculated.…”
Section: Literature Survey and Data Extractionmentioning
confidence: 99%
“…Our effort yielded 3,378 unique associations in 5,564 records between 1,776 carabid and 676 fungal species. Although rapidly developing molecular methods have largely facilitated the mapping of complex interaction networks in ecological studies 25 27 , due to the historic nature of our dataset, most of the records rely on traditional taxonomical identification. Yet, 16 records were based purely on metabarcoding studies; comments linked to these associations clearly identify them.…”
Section: Background and Summarymentioning
confidence: 99%
“…Thus, in the last decade, metabarcoding has emerged as an invaluable molecular tool for characterising diet breadth in polyphagous predators. It offers unique opportunities for deciphering trophic interactions within food webs 61 . Nonetheless, this gain in trophic network understanding comes at the cost of accuracy and sensitivity for target species detection 62 .…”
Section: Discussionmentioning
confidence: 99%